Psalm 151 of the Septuagint: a Subject Analysis - Veviurko Il'ia (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия I. Богословие, философия, 2016)
By its location in the Septuagint canon, Psalm 151 takes up a place of a certain epilogue of the whole Psalter. Due to its isolation in the Greek text and non-canonicity from the masoretic point of view, as well as to its apparent simplicity and triviality, the Psalm was not often attracting attention of the biblical scholars. Only after discovering of a longer Hebrew version of the Psalm in Qumran the situation began to change. Now the Greek Ps 151 has being engaged into comparative study, but generally remaining in the shadow of the Qumran text. This article deals principally with Septuagint version of the Psalm, that underlies the Slavonic and others recensions adopted in the Christian tradition. A through thematical analysis, beginning with the presumption of the texts meaningfulness, will allow then to compare it with the longer Qumran version, the latter to be found poetical interpretation of the former. The analysis reveals David of the Ps 151 to be very much archetypical than historical personality. This is enough to explain the almost complete withdrawal of the emotional «colours», though not depriving the Psalm of its poetical expressiveness. The hero of Ps 151 is a silhouette with some trates of the Anoited One that cometh. This conclusion leads us to the proper estimation of the signiﬁcance of the Psalm in the history of religious ideas: by the examination of this text we can determine more exactly, what kind of characteristics of the Psalters David collected in its ‘epilogue’ were perceived by the readers as protomessianic: the stainless moral purity, the unfamiliarity to the world, the mysterious conversation with God, the natural possession of power as a mode of the direct divine activity, and the readiness to became a ransomer for the people.